2014
DOI: 10.1002/macp.201400367
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Solvent Type on High‐Temperature Thermal Gradient Interaction Chromatography of Polyethylene and Ethylene–1‐Octene Copolymers

Abstract: The effects of the solvent type and operation conditions on the high‐temperature thermal gradient interaction chromatography (HT‐TGIC) of ethylene homopolymers, ethylene–1‐octene copolymers, and their blends are investigated. While the HT‐TGIC profiles of single polymers measured with 1,2,4‐trichlorobenzene (TCB) and chloronaphthalene (CN) are similar, they are always narrower when o‐dichlorobenzene (ODCB) is used, particularly for samples with lower 1‐octene fractions. Significant differences between the expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…When binary blends of ethylene/1‐olefin copolymers are analyzed by HT‐TGIC, sometimes copolymers of different compositions affect each other's HT‐TGIC profiles, a phenomenon that has been attributed to co‐adsorption and/or co‐desorption of these species. In a previous publication from our group, we showed that copolymer microstructure, analytical conditions, and type of the mobile phase influence these phenomenon. We also defined a co‐desorption index (CDI) to quantify these effects CDI=2×35 °C160 °C|(normaldwnormaldT)normalexp(normaldwnormaldT)normalpred|normaldTwhere (d w /d T ) exp and (d w /d T ) pred are the normalized heights of the experimental and calculated HT‐TGIC profiles of the blend at each data point, respectively.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…When binary blends of ethylene/1‐olefin copolymers are analyzed by HT‐TGIC, sometimes copolymers of different compositions affect each other's HT‐TGIC profiles, a phenomenon that has been attributed to co‐adsorption and/or co‐desorption of these species. In a previous publication from our group, we showed that copolymer microstructure, analytical conditions, and type of the mobile phase influence these phenomenon. We also defined a co‐desorption index (CDI) to quantify these effects CDI=2×35 °C160 °C|(normaldwnormaldT)normalexp(normaldwnormaldT)normalpred|normaldTwhere (d w /d T ) exp and (d w /d T ) pred are the normalized heights of the experimental and calculated HT‐TGIC profiles of the blend at each data point, respectively.…”
Section: Resultsmentioning
confidence: 83%
“…Monrabal et al [22] reported that the HT-TGIC peak position did not depend on molecular weight for polyethylene with M n higher than 25 000 g mol −1 . Alghyamah and Soares [23][24][25] used a set ethylene/1-octene copolymers with comonomer contents up to 3.5 mol% to study the effect of solvent type, sample injection volume, and adsorption/desorption temperature range on HT-TGIC chromatograms of individual samples and their blends. They showed that o-dichlorobenzene increased elution peak temperatures and had slightly better resolution than 1,2,4-trichlorobenze.…”
Section: Introductionmentioning
confidence: 99%
“…Chang et al were the first to use TGIC to fractionate polymers according to molecular weight as an alternative to gel permeation chromatography. 26 Al-Khazaal et al 27 and Alghyamah et al 28 investigated several parameters affecting HT-TGIC fractionation of polyolefins, such as polymer molecular weight and α-olefin fraction, heating rate, cooling rate, elution flow rate, support particle size, column length, solvent type, and type of packing material. These previous HT-TGIC investigations concentrated on polyethylenes with number average molecular weights, M n , higher than 25 000.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing heating rate leads to higher elution temperature (the temperature of the column will rise faster between the moment the polymer is desorbed and the moment it reaches the detector). Decreasing the elution rate results in higher elution temperature and broaden the TGIC profile probably due to an increased residence time in the column …”
Section: Introductionmentioning
confidence: 99%
“…Decreasing the elution rate results in higher elution temperature and broaden the TGIC profile probably due to an increased residence time in the column. [34][35][36] One of the key features of the TGIC profile is the broadening of the peaks at high α-olefins content. A similar feature was observed with TREF and it was attributed to the Stockmayer bivariate distribution of the copolymer chemical composition.…”
Section: Introductionmentioning
confidence: 99%